Pelatihan Pengenalan American English dan British English kepada Siswa/i SMA di Kota Batam - Ambalegin, Ambalegin; Handayani, Nurma Dhona; Salsabila, Lubna (ASOSIASI IDEBAHASA KEPRI, 2024)
A required and significant subject that high school pupils need to be proficient in is English. English puts more of an emphasis on communication skills than just providing the knowledge needed to pass a written exam. This makes students forget after that because the purpose of learning English is only to complete assignments rather than gaining communication skills. This training trains how to pronounce English words in American and British English. The training, which was attended by 104 participants, was carried out at SMA Putra Batam, SMA Muhammadiyah 1 Batam, SMAN 20 Batam, SMAN 25 Batam, and SMAN 15 Batam from November 2023 to January 2024. Service learning with models of lectures, discussions, and practice doing was the method. During the oral pre-test, 35 (33%) participants were able to pronounce the phoneme sounds in both American and British English. Then, from the oral post-test, 88 (84%) participants were able to pronounce the same phonemes in both English versions. 53 (51%) participants saw an improvement in their skills after training